Disaster Mitigation Due to Mining Activities (Case Study in Bongkaras Village, Silima Pungga-Pungga District, Dairi Regency) - Roida Boang Manalu; Nur Afifah (International Conference on Economic Business and Social Science, 2025)
Ecological disasters due to mining activities are a serious problem that has an impact on the environment and society. Bongkaras Village, which is located in Dairi Regency, precisely in Silima Pungga-Pungga District has experienced environmental degradation due to lead and zinc mining by PT Dairi Prima Mineral (PT DPM). Impacts such as water pollution, soil degradation, and increased risk of floods and landslides have threatened the sustainability of ecosystems and the livelihoods of local communities. Therefore, this study aims to analyze the disaster mitigation strategies implemented by the government and related parties in reducing the impact of mining in the area. This study uses a qualitative method with a descriptive approach. Data collection techniques through in-depth interviews, field observations, and documentation studies. The research informants included the village government, the Dairi Regency Regional Disaster Management Agency (BPBD), affected communities, and environmental activists from Brazil. Data analysis was carried out by source triangulation techniques and techniques to ensure the validity of the findings. William Nick Carter’s disaster mitigation theory is used as an analytical framework, covering six main aspects, namely : legal framework, institutions, public awareness, training and education, incentives, and early warning systems. The results of the study show that disaster mitigation in Bongkaras Village still faces various obstacles. Regulations related to environmental management have not been enforced optimally, government supervision of mining activities is still weak, and community participation in mining-related decision making is very minimal. The case of water pollution in 2012 and the flash flood disaster in 2018 are clear evidence that the mitigation carried out has not been effective. The public is also not fully aware of the long-term dangers of mining exploitation, while the early warning system is still not fully implemented. So it is necessary to strengthen regulations, increase transparency in mining management, and closer collaboration between the government, companies, and local communities. The government must strengthen the role of institutions and supervision so that the exploitation of natural resources no longer sacrifices environmental sustainability and community welfare.